Perlakuan Akuntansi untuk Aset Bersejarah - Wahyu Wunanto; Nur Chairunnisa A.Tantu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Historical assets are important assets for the culture of the community and the history of the nation as well as as the identity of the state. This research is a study on accounting treatment applied to historical assets in Indonesia which focuses on the analysis of accounting treatment in the management of the Central Sulawesi Museum. This study is a qualitative research within the scope of the interpretive paradigm of phenomenological studies on the results of interviews with research informants. The data analyzed were the results of interviews with academics, related agencies and the management of Sambisari Temple. The data was obtained through the interview process, documentation, documentation analysis, and online data search.